Legal Reformulation of Consensus-Based Neutrality Diplomacy in The Resolution of The South China Sea Dispute Based on The Perspective of National Defense and Security - Larasati, Kristina Bela; Hidayat, Arif (Universitas Negeri Semarang, 2025)
This study aims to analyze Indonesia's foreign policy in dealing with the South China Sea dispute and formulate a consensus-based neutrality diplomacy model from the national defense and security perspective. Although Indonesia is not a claimant country, the escalation of the conflict in the South China Sea, especially unilateral claims that overlap the Exclusive Economic Zone (EEZ) in the North Natuna Sea, directly threatens Indonesia's maritime sovereignty and national interests. This study uses normative legal research methods to examine how the neutrality principle can be reformulated legally into a more operational and responsive active neutrality approach. The study results indicate that the current neutrality diplomacy approach has not been sufficiently institutionalized to respond to complex geopolitical dynamics. Therefore, a legal reformulation model is proposed that integrates the principle of active neutrality into the legal framework of Indonesia's foreign policy. In conclusion, by institutionalizing consensus-based neutrality diplomacy, Indonesia can strengthen its position as an impartial but constructive mediator, protect its sovereign rights, and actively contribute to the peaceful and legal resolution of disputes in the region, in line with the mandate of the constitution and international law.